Comparison of Corneal Epitheliotrophic Factors of Undiluted Autologous Platelet-Rich Plasma and Autologous Serum Eye Drops for Dry Eye Disease - Passara Jongkhajornpong; Kaevalin Lekhanont; Sasivimol Rattanasiri; Prapaporn Pisitkun; Ammarin Thakkinstian (Ophthalmology and Therapy)
Abstract Introduction The purpose of this study was to compare the growth factor concentrations in undiluted autologous platelet-rich plasma (APRP) and autologous serum (AS) eye drops. Methods This was a single-center, prospective trial conducted in a tertiary university hospital in Bangkok, Thailand. Ninety-six patients with moderate-to-severe dry eye disease, who were randomly assigned to receive either 100% APRP or 100% AS, were enrolled in the study. Primary outcome measures were the concentrations of epitheliotrophic factors, including epithelial growth factor (EGF), basic fibroblast growth factor (bFGF), hepatocyte growth factor (HGF), β-nerve growth factor (β-NGF), platelet-derived growth factor (PDGF)-AA, PDGF-BB, transforming growth factor (TGF)-α, TGF-β1, and vascular endothelial growth factor (VEGF) in 100% APRP and 100% AS. Secondary outcome measures were the correlations between baseline patient characteristics and each growth factor concentration. Results Undiluted APRP contained more EGF, bFGF, and β-NGF than undiluted AS (P < 0.001, P < 0.001, P = 0.018, respectively). Meanwhile, undiluted AS yielded higher concentrations of HGF, PDGF-AA, PDGF-BB, and VEGF compared with undiluted APRP (P < 0.001 all). There were no significant differences in TGF-α and TGF-β1 concentrations between the two groups. In the 100% APRP group, the platelet concentrations had positive correlations with the concentrations of EGF (P = 0.028) and VEGF (P = 0.020). In the 100% AS group, Sjögren’s syndrome negatively correlated with the concentrations of PDGF-BB (P = 0.028) and VEGF (P = 0.023). Diabetes mellitus (DM) showed negative correlations with the concentrations of HGF (P = 0.001), TGF-α (P = 0.001), and VEGF (P = 0.002). Conclusions With our simple preparation protocols, 100% APRP contains higher concentrations of EGF, bFGF, and β-NGF, whereas 100% AS contains higher concentrations of HGF, PDGF-AA, PDGF-BB, and VEGF. This could allow ophthalmologists to tailor treatments to individual patients by targeting growth factor supply based on their underlying pathophysiology. Trial registration ClinicalTrials.gov identifier, NCT04683796.